Cholera risk in cities in Uganda: understanding cases and contacts centered strategy (3CS) for rapid cholera outbreak control - Bwire, Godfrey; Waniaye, John Baptist; Otim, Julius Simon; Kagirita, Atek; Orach, Christopher Garimoi (Pan African Medical Journal, 2021)
in the recent past, cities in sub- Saharan Africa have reported serious cholera outbreaks that last for several months. Uganda is one of the African countries where cities are prone to cholera outbreaks. Studies on cholera in Bangladesh show increased risk of cholera for the immediate household members (contacts) yet the control interventions mainly target cases with little or no focus on contacts. This study aimed to describe the rapid control of cholera outbreaks in Kampala and Mbale cities, Uganda, using, “Cases and Contacts Centered Strategy (3CS)” that consisted of identification and treatment of cases, promotion of safe water, sanitation, hygiene (WaSH) and selective chemoprophylaxis for the contacts.